Positive Effects of Practical Nutrition Lessons in a Primary School Setting with a High Proportion of Migrant School Children - Weber, Katharina S.; Eitner, Jessica; Dauben, Laura; Spörkel, Olaf; Strassburger, Klaus; Sommer, Jörn; Kaiser, Barbara; Buyken, Anette E.; Kronsbein, Peter; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Children with migration background are at increased risk for overweight, partly due to less favorable dietary habits compared to their German counterparts. We examined the effects of practical nutrition lessons among children with a high proportion of migration background in a primary school setting.Methods Ten 3rd and 4th grade classes (n=166 children, 73% with migration background) received the intervention and nine school classes (n=139 children, 76% with migration background) served as control. Before, shortly after (only among the intervention group) and three months after the three-day practical nutrition lessons, the nutrition-related skills, behavior, attitudes, and knowledge of the children were assessed using a questionnaire. Changes between baseline and 1st follow-up among children of the intervention group were calculated using linear mixed models. Differences between the two groups for changes between baseline and 2nd follow-up were tested using linear regression analyses. Models were adjusted for potential confounders.Results Shortly after the practical nutrition lessons, the children of the intervention group had improved their knowledge (β=1.7; 95% CI: 1.0; 2.4, P<0.001) and skills (β=1.8; 95% CI: 1.4; 2.2, P<0.001). These changes were sustainable and larger in the intervention compared to the control group (knowledge: β=1.6; 95% CI: 0.7; 2.5, P<0.001; skills: β=1.3; 95% CI: 0.7; 1.9, P<0.001). Changes in nutrition-related behavior and attitudes did not differ between the groups.Conclusions Providing practical nutrition lessons in a primary school setting with a high proportion of children with immigrational background improved the children’s nutrition-related knowledge and skills.
Keywords: lifestyle intervention; prevention; migration background